Penerapan Kompetensi Profesional Guru Pendidikan Agama Islam (PAI) dalam Meningkatkan Keterampilan Berpikir Kritis Siswa - Akhyar, Muaddyl; Sesmiarni, Zulfani; Febriani, Susanda; Aulia Gusli, Ramadhoni (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research emphasizes the importance of teachers' professional skills to improve students' critical thinking skills, especially in the 21st century, where these skills are crucial. This study used a qualitative research method with a literature study approach. The purpose of this study is to see how the application of PAI teachers' professional competence in helping students improve their critical thinking. The results of this study show that teachers' professional competence has a significant impact on improving students' critical thinking skills. However, it was found that Islamic Religious Education (PAI) teachers still do not fully master the material. They also lack creativity in developing learning materials and rarely connect PAI materials with other sciences. Some teachers do not even use learning media at all because they do not have equipment such as projectors, so they use blackboards. Students can become bored and not understand the lesson if there is no learning media